2023
DOI: 10.3390/agronomy13122963
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Physiological Traits and Gene Expression of Brassinosteroids Signaling under Drought Conditions in Two Chickpea Cultivars

Khatereh Felagari,
Bahman Bahramnejad,
Adel Siosemardeh
et al.

Abstract: This study aimed to investigate the effects of drought stress at the flowering stage on the physiological and molecular responses of the genes involved in the brassinosteroid pathway of two chickpea cultivars (ILC1799: drought tolerant, and ILC3279: drought sensitive). The drought resulted in significant reductions in chlorophyll a, chlorophyll b, total chlorophyll and carotenoid content in both cultivars, and had significantly lesser effects on the tolerant cultivar, Samin, compared to that of ILC3279. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Chlorophyll is a vital pigment involved in photosynthesis, which is one of the most significant anabolic processes in plants and is the first physiological process to be affected by drought stress [97]. Under drought conditions, the chlorophyll content decreases, the photosynthetic capacity declines, and photosynthesis weakens due to leaf wilting [98,99].…”
Section: Drought Stress and Brsmentioning
confidence: 99%
“…Chlorophyll is a vital pigment involved in photosynthesis, which is one of the most significant anabolic processes in plants and is the first physiological process to be affected by drought stress [97]. Under drought conditions, the chlorophyll content decreases, the photosynthetic capacity declines, and photosynthesis weakens due to leaf wilting [98,99].…”
Section: Drought Stress and Brsmentioning
confidence: 99%
“…At the same time, another study showed that the proline content of the '82-7 ′ variety was much higher than that of the other varieties and lines with weak tolerance to shriveling in hybrid hazelnut during overwintering, and the proline content of 'Dawei' was second to that [6]. In summary, the drought tolerance of hybrid hazelnuts was closely related to their proline content [7]. Osmoregulation is a stress response that enhances the resistance of plants to osmotic stress.…”
Section: Introductionmentioning
confidence: 96%